A vicious cycle of manias, crashes and asymmetric policy responses : an overinvestment view - Andreas Hoffmann; Gunther Schnabl (Center for Economic Studies and ifo Institute (CESifo), 2009)
The business cycles theories of Wicksell (1898), Schumpeter (1912), Mises (1912), Hayek (1929, 1935) and Minsky (1986, 1992) explain business cycles by distorted prices on capital markets, buoyant credit expansion and overinvestment. The exuberance during the boom endogenously causes the subsequent slump. While these theories put the emphasis on explaining the emergence of the cycle, this paper focuses on the macroeconomic policy responses during and after the crisis, when panic tightens credit supply. The paper allows an assessment of the long-term consequences of an asymmetric monetary and fiscal policy response to financial crisis.
Keywords: B53; E32; E44; E63; 330; Konjunkturtheorie; Finanzmarktkrise; Konjunkturpolitik; Makroökonomischer Einfluss; Theorie